Old and New Actors and Phenomena in the Three-M Processes of Life and Society: Medicalization, Moralization and Misinformation - Alarcão, Violeta; Pintassilgo, Sónia Cardoso (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Over the last 50 years, people's lives and health have been increasingly defined and influenced across the life course and across levels of influence by different processes of medicalization and social control. Although medicalization is not a new concept, new actors, in addition to medical professionals and patients, and new phenomena, such as consumerism and human enhancement, influence the processes of the transformation of human conditions into medical problems today. This reprint integrates several articles that stimulate reflexivity on the use of the concept of medicalization. The articles selected for this reprint, written by research experts in their topic of interest, contribute to the discussion on the wide variety of ethical issues that arise from medicalization processes in areas ranging from medical research conduct to reproductive health. The reader will find a fertile space for theoretical and empirical reflection, where several social science researchers with different backgrounds share their research rigorously and innovatively.